2007
DOI: 10.1261/rna.666807
|View full text |Cite
|
Sign up to set email alerts
|

Improved amber and opal suppressor tRNAs for incorporation of unnatural amino acids in vivo. Part 1: Minimizing misacylation

Abstract: The incorporation of unnatural amino acids site-specifically is a valuable technique for structure-function studies, incorporation of biophysical probes, and determining protein-protein interactions. THG73 is an amber suppressor tRNA used extensively for the incorporation of >100 different residues in over 20 proteins, but under certain conditions THG73 is aminoacylated in vivo by endogenous aminoacyl-tRNA synthetase. Similar aminoacylation is seen with the Escherichia coli Asn amber suppressor tRNA, which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
(105 reference statements)
1
29
1
Order By: Relevance
“…As such, we cannot state with confidence what role this residue might play. We note that previous experiments have shown that the amino acid incorporated by misacylation of the THG73 tRNA is most likely Gln (45). If that is the case here, the mere 10-fold shift in EC 50 for what is effectively a W3.28Gln mutation is too small to be consistent with a cation-interaction.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…As such, we cannot state with confidence what role this residue might play. We note that previous experiments have shown that the amino acid incorporated by misacylation of the THG73 tRNA is most likely Gln (45). If that is the case here, the mere 10-fold shift in EC 50 for what is effectively a W3.28Gln mutation is too small to be consistent with a cation-interaction.…”
Section: Discussioncontrasting
confidence: 50%
“…If that is the case here, the mere 10-fold shift in EC 50 for what is effectively a W3.28Gln mutation is too small to be consistent with a cation-interaction. We also note that more recently developed tRNAs that are less prone to acylation may allow study of the W3.28 site (45,46).…”
Section: Discussionmentioning
confidence: 95%
“…THG73 (23) and TQOpSЈ (24,25) were used as amber suppressor tRNA and opal suppressor tRNA, respectively. Conjugated dCA-amino acid was ligated to 74-nucleotide tRNA as previously reported (21).…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the possibility of a Phe-Pro interaction in this system by testing double mutant receptors in which Phe 135 was substituted with the non-aromatic Cha and Pro 136 was substituted with either Pip or 3-MePro, the two mutations that cause the largest EC 50 shifts. These experiments required consecutive incorporation of two different unnatural amino acids, an unprecedented experiment for receptors expressed in a living cell that was made possible by recent advances in tRNA design (24,25). The resulting current signals (1-4 A) were quite sufficient for quantitative analysis.…”
Section: Mutational Studies At Phementioning
confidence: 99%
“…Like amber suppressors, opal and ochre tRNAs are usually derived from a native scaffold in which the anticodon and/or adjacent bases have been mutated to pair with a UGA or UAA codon, respectively (Köhrer et al 2004). tRNA Phederived opal and ochre tRNAs have been used to incorporate nitrophenylalanine in rabbit reticulocyte lysate (RRL) (Taira et al 2005), and opal suppressors derived from tRNA Gln or tRNA Trp have been used to incorporate 5-hydroxytryptophan (Zhang et al 2004) and 5-F-tryptophan (Rodriguez et al 2007), respectively, in mammalian cells. Ochre suppressors derived from Escherichia coli supF tRNA and the suppressors of all three nonsense codons derived from E. coli tRNA Gln have also been used to incorporate tyrosine (Köhrer et al 2003) and glutamine (Köhrer et al 2004) residues in mammalian cells, respectively.…”
Section: Introductionmentioning
confidence: 99%